ANALISIS KELAYAKAN PEMBIAYAAN TERHADAP TINGKAT PENGEMBALIAN PEMBIAYAAN USAHA KECIL PADA BANK SYARIAH INDONESIA: Analisis Kelayakan Pembiayaan terhadap Tingkat Pengembalian Pembiayaan Usaha Kecil pada Bank Syariah Indonesia - Ali, Mohamad (jsd: Journal of Society and Development, 2025)
In an era of expanding financial access and increasingly competitive MSME financing, the feasibility assessment of financing has become a crucial determinant of portfolio performance in Islamic banking. This study aims to empirically analyze the effect of financing feasibility on the repayment rate of small-business financing at Bank Syariah Indonesia (BSI). A quantitative research design was employed through survey distribution to 180 MSME recipients of BSI financing, complemented by in-depth interviews with financing officers to enhance data validity. Four dimensions of feasibility were examined technical feasibility, market feasibility, financial feasibility, and financing analysis quality. The collected data were analyzed using multiple linear regression to measure the significance and contributive strength of each variable on repayment performance, indicated by installment smoothness. The results reveal that all four feasibility variables exert a positive and significant influence on repayment performance. Financial feasibility emerged as the dominant factor (β = 0.431), while the coefficient of determination (R² = 0.614) indicates that 61.4% of repayment variation is explained by the model. Additional findings highlight that digital transaction recording and continuous post-disbursement mentoring are associated with higher repayment consistency. This study affirms the urgency of strengthening feasibility assessment, improving debtor financial literacy, and integrating digital-based data analysis as strategic measures for optimizing MSME financing risk management within the Islamic banking system.